Assessing endometrial receptivity after recurrent implantation failure: a prospective controlled cohort study. Issue 6 (December 2020) - Saxtorph, Malene Hviid; Hallager, Trine; Persson, Gry; Petersen, Kathrine Birch; Eriksen, Jens Ole; Larsen, Lise Grupe; Hviid, Thomas Vauvert; Macklon, Nick
Abstract: Research question: What is the prevalence of disrupted markers of endometrial function among women experiencing recurrent implantation failure (RIF), and does the prevalence differ from a control cohort? Design: Prospective controlled cohort study. In total, 86 women with a history of RIF and 37 women starting their first fertility treatment were recruited for this study. Endometrial and blood profiling were carried out in a hormone-substituted cycle using oestradiol and progesterone. Endometrial biopsies were analysed by histology, immune cell profiling, and the endometrial receptivity array (ERA®) test (Igenomix, Valencia, Spain). The vaginal microbiome was analysed using a NGS-based technology (ArtPRED, Amsterdam, the Netherlands). Blood tests included oestradiol, progesterone, prolactin, thyroid-stimulating hormone, vitamin D and anti-phospholipid antibody levels. Results: Patients who had experienced RIF produced a range of test abnormalities. Compared with controls, women with RIF had a higher prevalence of chronic endometritis (24% versus 6%), a lower vitamin D level and a borderline lower progesterone level. Women who had experienced RIF had a more favourable vaginal microbiome compared with controls. Although the RIF cohort was older than the controls (mean age 33.8 years versus 30.2 years), no differences between the groups were observed in immune cell profiling and the ERA test. Conclusion: These data demonstrate that a single test or treatment for the endometrial factor in RIF is unlikely to be clinically effective. Diagnosing the endometrium in women with RIF permits targeted rather than blind interventions. Relative vitamin D deficiency, lower mid-luteal progesterone and chronic endometritis are ready targets for treatment. Understanding the role and treatment of an unfavourable vaginal microbiome in RIF needs further investigation.